Advances in the study of the impact of the hypoxic plateau environment on tumor initiation, progression, and molecular mechanisms - Guo Jing; Shi Jinfen; Li Yufan; Shi Bing (生物医学转化, 2025)
The hypoxic plateau environment has a broad impact on human physiological function, and its role in tumor initiation and progression has attracted increasing attention in recent years. This review focuses on the effects of the hypoxic plateau environment on tumor biological behavior through the hypoxia-inducible factor (HIF) signaling pathway, oxidative stress response, and changes in the immune microenvironment. Studies have shown that continuous hypoxia can stabilize the expression of HIF-1α, thereby regulating downstream target genes and affecting tumor angiogenesis, energy metabolic reprogramming, and resistance to apoptosis. At the same time, the synergistic effect of strong ultraviolet radiation and hypoxia in the plateau environment can increase the production of reactive oxygen species (ROS), leading to DNA damage and genomic instability. In addition, the hypoxic plateau environment can induce increased myeloid-derived suppressor cell (MDSC) infiltration and upregulation of PD-L1 expression, promoting tumor immune escape. This paper also summarizes tumor prevention strategies for the hypoxic plateau environment, including targeted interventions in the HIF pathway, antioxidant therapy, and immunomodulation, aiming to provide a scientific basis for tumor prevention and treatment in plateau regions.